2010
DOI: 10.5120/1688-1845
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Rectangular and U Slotted Patch for Satellite Communication

Abstract: This paper presents Microstrip antenna in the application for a satellite band microwave communication system for super high frequency (SHF), at a frequency range of 4.0 Ghz -6.0Ghz. Currently, most security, research and education platforms are equipped with SHF communication systems. For their operational requirements, a design study is needed for the development of a light weight, low volume, low profile antenna. Hence, in this paper, bandwidth enhancement techniques such as, use of various substrate with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…However, the other parameters affect the radiation where the optimal empirical patch length and width are found to be 6mm and 9mm respectively. These values are in a very good agreement with the calculated ones using 10GHz operation frequency in the following equations [17,18]:…”
Section: Preliminary Designsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the other parameters affect the radiation where the optimal empirical patch length and width are found to be 6mm and 9mm respectively. These values are in a very good agreement with the calculated ones using 10GHz operation frequency in the following equations [17,18]:…”
Section: Preliminary Designsupporting
confidence: 87%
“…Since the patch design, in general, plays important role in the antenna radiation, different patch shapes have been considered to enhance the antenna bandwidth and efficiency [9,10], though introducing a slot into a simple patch shape is much more practical as it is very easy and can enhance the antenna fringing significantly [3]. Therefore, many studies have demonstrated slots in simple rectangular patch, but the maximum bandwidth achieved is still relatively low (< 5GHz) [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Approximate the center frequency as (fres3) and the lower and upper frequency bounds of the bandwidth as (fres2) and (fres4) respectively. Select a substrate permittivity (ε r ) and a substrate thickness h. According to the following relationship [2]:…”
Section: Design Proceduresmentioning
confidence: 99%
“…Microstrip patch directional antennas have been used in many applications [14] - [16], because of their low profile, conformability, light weight, easy connectivity (feed), cheap realization and attractive radiation characteristics. A microstrip patch antenna is a wide-beam, narrowband antenna which is created by etching the antenna element (patch) in a metal trace material bonded to an isolating dielectric substrate [17]. Most physical realizations feature a Printed Circuit Board (PCB), with a continuous metal layer attached to the opposite side of the substrate which creates a ground plain.…”
Section: Microstrip Patch Antennamentioning
confidence: 99%